2011
DOI: 10.1016/j.chroma.2011.03.032
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of sampling time effects on the resolving power of on-line two-dimensional high performance liquid chromatography

Abstract: The experimental effects of sampling time on the resolving power of on-line LC×LC were investigated. The first dimension gradient time (1tg) and sampling time (ts) were systematically varied (1tg = 5, 12, 24 and 49 min; ts = 6, 12, 21 and 40 s). The resolving power of on-line LC×LC was evaluated in terms of two metrics namely the numbers of observed peaks and the effective 2D peak capacities obtained in separations of extracts of maize seeds. The maximum effective peak capacity and number of observed peaks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 42 publications
(120 reference statements)
2
36
0
Order By: Relevance
“…The procedure is based on a painstaking visual inspection of each individual second dimension chromatogram and the manual merging of peaks that correspond to the same first dimensional peak. This procedure has been described in detail 4 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure is based on a painstaking visual inspection of each individual second dimension chromatogram and the manual merging of peaks that correspond to the same first dimensional peak. This procedure has been described in detail 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Previously we and others have shown that in this form of LC×LC there is necessarily an optimum sample acquisition time 4, 5 . In on-line LC×LC this sampling time ( t s ) must be equal to the second dimension cycle time ( 2 t c ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In practice, the effective peak capacity is lower for several reasons, including the difficulty in choosing a pair of columns which maximize the use of the 2D separation space [3], partially due to the lack of orthogonality between commercially available columns [4], and the undersampling of the first dimension separation [5]. Despite these limitations Stoll, Wang, and Carr determined through both theoretical and experimental studies that when separation times are greater than 10 min and the 2 D separation is conducted sufficiently rapidly, LC Â LC has superior effective peak capacity as compared to 1D-LC [5][6][7][8]. While multi-dimensional chromatography has definite advantages in terms of peak capacity and peak capacity per unit time, the precision and accuracy of these methods compared to 1D chromatography often are not considered.…”
Section: Introductionmentioning
confidence: 96%
“…The concept of LC × LC was introduced three decades ago; the enormous improvements since 1990 have confirmed the huge potential of LC × LC for increasing peak capacity; this mainly results from the “multiplicative advantage” of multi-dimensional methods under ideal conditions [12-17]. Recently, Carr and coworkers performed a series of LC × LC studies on metabolomics samples with total analysis times in the range of 15–60 min [18-20] but with the second dimension run on the time scale of 6–40 s by doing the second dimension separations at high temperatures (100–120 °C). The decreased eluent viscosity at higher temperatures makes it possible to use high linear velocities, high flow rates (~3 mL/min) and short cycle times on the second dimension.…”
Section: Introductionmentioning
confidence: 99%